Work disability in the United States, 1968-2015: Prevalence, duration, recovery, and trends - James N. Laditka; Sarah B. Laditka (Elsevier, 2018)
The United States workforce is aging. At the same time more people have chronic conditions, for longer periods. Given these trends the importance of work disability, physical or nervous problems that limit a person's type or amount of work, is increasing. No research has examined transitions among multiple levels of work disability, recovery from work disability, or trends. Limited research has focused on work disability among African Americans and Hispanics, or separately for women and men. We examined these areas using data from 30,563 adults in the 1968-2015 Panel Study of Income Dynamics. We estimated annual probabilities of work disability, recovery, and death with multinomial logistic Markov models. Microsimulations accounting for age and education estimated outcomes for African American, Hispanic, and non-Hispanic white women and men. Results from these nationally representative data suggested that the majority of Americans experience work disability during working life. Most spells ended with recovery or reduced severity. Among women, African Americans and Hispanics had less moderate and severe work disability than whites. Among men, African Americans became severely work disabled more often than whites, recovered from severe spells more often and had shorter severe spells, yet had more severe work disability at age 65. Hispanic men were more likely to report at least one spell of severe work disability than whites; they also had substantially more recovery from severe work disability, and a lower percentage of working years with work disability. Among African Americans and Hispanics, men were considerably more likely than women to have severe work disability at age 65. Work disability declined significantly across the study period for all groups. Although work disability has declined over several decades, it remains common. Results suggest that the majority of work disability spells end with recovery, underscoring the importance of rehabilitation and workplace accommodation. Keywords: United States, African Americans, Hispanics, Disability, Recovery, Work disability, Microsimulation